Electrochemical characteristics of nano-silicon/graphite composite for the anode material of lithium secondary batteries - Lee, JK; Park, TJ (TRANS TECH PUBLICATIONS LTD, 2006)
Silicon coated graphite particles prepared by gas suspension spray method were used as a raw material for the battery anode, which showed high specific capacity and good cycle performance. The improvement of electrochemical performance seems to be due to the formation of amorphous silicon-carbon black composite layer on the surface of the graphite particles. It has a stable structure under repeated volume expansion and contraction.